Notice that you can divide the first equation by 2 to simplify the system:
2x-3y=6

-2x+3y=-6

Add the first equation to the second to get the following system:

2x-3y=12

0=0

Therefore, this system reduces to the equation 2x-3y=12

Since we have 1 equation and 2 unknowns, we put y=t (we designate it as a parameter of this system), and get

\(\displaystyle{2}{x}-{3}{t}={12}\to{2}{x}={3}{t}+{12}\to{x}={1.5}{t}+{6}\)

Therefore, the solution is

x=1.5t+6, y=t, t is a parameter.

-2x+3y=-6

Add the first equation to the second to get the following system:

2x-3y=12

0=0

Therefore, this system reduces to the equation 2x-3y=12

Since we have 1 equation and 2 unknowns, we put y=t (we designate it as a parameter of this system), and get

\(\displaystyle{2}{x}-{3}{t}={12}\to{2}{x}={3}{t}+{12}\to{x}={1.5}{t}+{6}\)

Therefore, the solution is

x=1.5t+6, y=t, t is a parameter.